Reality producers of Bastos/SP about animal welfare and legislation in the commercial posture - De Sousa, Gabriela Pinheiro [UNESP]; Pereira, Danilo Florentino [UNESP]; Watanabe, Kássia [UNESP]; Cataneo, Pedro Fernando [UNESP] (American Society of Agricultural and Biological Engineers (ASABE), 2016)
The main focus of posture poultry is productivity. However, issues related to the welfare of the laying hens in the different production systems haves risen worldwide. Brazil produces quarterly about 700 million dozen chicken eggs and, the largest concentration is in the southeast region of the country. There are national and international protocols that deal with technical specifications to meet the best practices and poultry welfare. Thus, this article aims to analyze the perception of egg producers on animal welfare issues in the region of Bastos/SP. A structured interview with eighteen egg producers was applied, covering technical issues to capture the different opinions of producers and which has been applied in the establishments on welfare. It could be concluded that the producers already comply with several technical points of production that are provided by good practice protocols and welfare. However, some points, even if met by producers, lack standardization, which would be extremely viable to meet a high level of welfare. It is necessary to encourage the implementation of best practices by producers.
Keywords: Animal welfare; Good agriculture practices; Perception of producers; Poultry posture